Estudio Polarimétrico en la región de Centauro: NGC 5662 - Vergne, Maria Marcela (2016)
This paper shows the preliminary results of the polarimetric observations obtained in BVRI bands on a sample of 70 stars towards the regionof open cluster NGC 5662 in Centaurus.